Carbon credit for sustainable developement - Mishra, Amit; Jain, Ravi; Afrin, Huma; Sinha, Abhya Anjan (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The Greenhouse Gases which include Carbon dioxide, Methane and also other oxides on account of incomplete combustion substantially disturb the balance of the heat in the earth’s atmosphere leading to warming of the atmospheric temperature which is called as Global Warming and considered a major threat to life on earth. In today’s world situation, it is very much necessary to find out the solution for the global impact of pollution for the survival of life. The rules & regulations which are meant for the control of pollution are seen to be somewhat ineffective. One of the reasons behind the failure of such systems is that there are no attractive proposals in front of industries. The solution requires obviously the attraction in terms of economy. With this, the Kyoto Protocol, 1997, supported by United Nations Framework Convention on Climate Change (UNFCCC) gave a wonder full solution which may prove to be the golden midway between the reduction in pollution & the economy. Sustainable and clean renewable energy systems such as hybrid solar/wind electric generators can be used to eliminate or reduce carbon dioxide emissions by replacing old diesel, oil, gas or coal fired electric generators which emit greenhouse gases that produce global warming. Carbon sequestration credits or offsets are calculated by the amount of carbon emissions that would have been emitted if a diesel or other traditional polluting electric generator was used to produce the same amount of electricity. Companies and electric utilities in countries can buy these emission reduction carbon credits to replace the emissions from their coal burning electric power plants to meet regulatory requirements. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>